Immunoglobulin A (IgA) Nephropathy in Protocol Graft Kidney Biopsy done at six months Post Transplantation in a Tertiary Care Center Hospital of Nepal - Shrestha, Midhan; Shah, Dibya Singh (Journal of Nobel Medical College, 2017)
Background: Renal transplantation is the treatment of choice for end stage renal disease. The focus of interest has been to increase the life of the transplanted graft. Recurrence of native kidney disease or occurrence of denovo glomerulonephritis has adverse effects in graft survival. Protocol graft biopsy done at fixed time interval after transplantation aids in early identification of post-transplant glomerulonephritis before development of clinical signs and symptoms. This study describes the incidence of post-transplant IgA Nephropathy in protocol renal graft biopsies done at six months post- transplantation. Materials and Methods: This is a hospital based observational descriptive study, done in Tribhuvan University Teaching Hospital, Kathmandu, Nepal, a tertiary medical referral center in the capital. Protocol biopsy of the graft kidney was performed at six months post-transplantation in all recipients who underwent kidney transplantation in this hospital between 2071 Kartik and 2072 Ashwin. Results: Protocol biopsy was performed in total 47 recipients. Mean age of the recipients was 33.7 years ±10.83 years. The study population consisted of 33 (70.2%) male and 14 (29.8%) female recipients. IgA Nephropathy was present in 6 (12.8%) recipients. Conclusion: Our study demonstrates that IgA Nephropathy does occur in patients with stable GFR and without any clinical or laboratory abnormalities. Protocol biopsy is valuable in detection of early histologic abnormalities before onset of clinical manifestations, thus helping in prompt management with aim to prolong the graft survival. Journal of Nobel Medical College Volume 6, Number 1, Issue 10 (January-June, 2017)